Effects of pre-strain on sensitization and interganular corrosion for 304 stainless steel. (December 2019) - Zhang, Xuewen; Tang, Jianqun; Liu, Hao; Gong, Jianming
Abstract: The degree of sensitization (DOS) and the susceptibility to interganular corrosion (IGC) were investigated for pre-strained 304 stainless steel (SS) following thermally aged at 750 °C for one hour. The maximum pre-strain applied to the steel is 20%.The microstructures of 304 SS subjected to pre-strain and thermal aging were observed. The volume fraction of strain-induced α'-martensite and the vickers hardness were measured, respectively. The double loop electrochemical potentiokinetic reactivation (DL-EPR) tests were used to characterize the DOS as a function of various pre-strain levels. The tests in copper‑copper sulfate‑sulfuric acid (16%) solution were performed to evaluate the susceptibility to IGC. The morphologies of the cracks caused by IGC were observed. The results show, although pre-strained 304SS had been thermally aged at 750 °C for one hour, strain-induced α'-martensite and shear bands in steel are most retained and increase with pre-strain, causing the strengthening effect and leading to the increase in hardness. The DOS and the susceptibility to IGC also increase with pre-strain. The higher the value of the DOS is, the more serious IGC becomes. Obvious intergranular cracks as well as the dissolution of grain boundaries and the grains began to appear in the steel with 5% pre-strain, and the attack had been deteriorated with the increasing pre-strain. When the pre-strain is reached 20%, the longest crack is about 250 μm and its width is about 38 μm, indicating that the severe IGC had occurred. No obvious reversion of martensite to austenite and desensitization occurred for 304 SS withstood the maximum pre-strain up to 20% and thermally aged at 750 °C for one hour. Highlights: For 304 SS, strain-induced α′-martensite and shear band increase with pre-strain and most of them are retained after aging. The strengthening effect for the pre-strained specimen after thermal aging is retained. Pre-strain within 20% has great effects on the DOS and IGC for 304 SS, and the degrees increase with pre-strain. Aging after pre-strain for 304 SS does not cause the obvious reversion of martensite to austenite and desensitization.